Gut microbiota signatures in tissues of the colorectal polyp and normal colorectal mucosa, and faeces - Zhong, Xiaohui; Wang, Yuanyuan; Xu, Jianmin; Cao, Hong; Zhang, Feng; Wang, Xuesong (Frontiers in Cellular and Infection Microbiology, 2023)
Background Colorectal polyps are the most common precursors of colorectal cancer (CRC). The close relationship has been observed between colorectal polyps and gut microbiota. However, gut microbiota signatures among sampling sites in patients with colorectal polyps and healthy adults remain elusive. Aims To learn about gut microbiota signatures in tissues of the colorectal polyp and normal colorectal mucosa, and faeces. Methods We performed 16S rRNA gene sequencing and bioinformatic analysis for the microbiota in the normal colorectal mucosa, the colorectal polyps and faeces of adults with colorectal polyps (n = 24) and in faeces and normal mucosa of healthy adults (n = 16) in this preliminary trial. Results The Ace and Chao indexes were higher in the normal colorectal mucosa and polyp tissues compared to faecal samples (P < 0.05). The composition of microbiota based on PCoA and ANOSIM analysis showed the significant differences only between faeces and tissues of the normal mucosa and polyp (P < 0.05). Based on the LEfSe analysis, the abundances of Bacteroides, Prevotella-2 and Agathobacter were higher, whereas the abundances of Haemophilus, Escherichia_Shigella, Fusobacterium and Streptococcus were lower in faeces both in patients with colorectal polyp and healthy individuals, compared with those in the normal mucosa in two groups or polyp tissues. In healthy individuals, the abundance of Fusobacterium was significantly higher in the normal colorectal mucosa than in faeces. Moreover, there was no significant difference in the abundance of Fusobacterium between the normal colorectal mucosa and polyps in patients with colorectal polyps, but it was significantly higher in the mucosa and polyps than in faeces. Remarkably, the abundance of Fusobacterium in the normal colorectal mucosa was significantly higher in healthy individuals than in the polyp group. Conclusions The microbial structure in faeces differs from that in tissues of polyp and normal mucusa. Additionally, Fusobacterium may be a normal colonizer in colonic mucosa, and an abnormal increase of Fusobacterium detected in faeces may be related with the injury of the colorectal mucosa. The difference of the faecal microbiota and mucosal microbiota should be carefully considered in studies on gut microbiota in patients with colorectal lesions.